Properties of dehydrated cassava puree and wheat flour blends and its relationship with the texture of doughs - Cazzaniga, Amanda (2017)
Fil: Cazzaniga, Amanda. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.